Analyzing user learning experience based on physiology measurement / Raihah Aminuddin - Aminuddin, Raihah (2013)
The physiology measurement has received many attentions from researcher for over a century. Many studies also describes the physiological measurement as responding to all kinds of psychological states such as emotions. The emotional states can be indicated by different of arousal levels under different circumstances and the changes in physiological in response to specific event such as learning. However, studies on the emotion in learning using physiology measurement is still under emphasized. Therefore, the purpose of this study is to measure the user emotion in learning experience with the used of mobile learning application based on physiology measurement. The physiological measurement has been used in the study are skin conductance and blood volume pressure. The result form the analysis of physiological data has discovered the types of emotions and the level of arousal produced by the participants. Each result produced by participants are unique. Based on the findings, there are few types of emotion has been produced during learning process such as bored, disappointment, confused, happy, satisfy and interest. This study also highlight the importance of considering emotion in learning. As a result, the further research on physiology measurement and learning experience can be donein future based on the finding in this study.